Agricultural dust explosions in 2009 - Ambrose, R. P. Kingsly (Kansas State University. Dept. of Grain Science and Industry, 2015)
There were 8 dust explosions reported in the U.S. in 2009 according to Kingsly Ambrose, Assistant Professor, Kansas State University. This compares to 19 in 2008 and a ten-year average of 9.5 explosions.
Keywords: Grain dust; Dust explosions